Plants of an Eucalyptus clone damaged by Scolytidae and Platypodidae (Coleoptera) - Zanuncio, José Cola; Sossai, Marcos Franklin; Flechtmann, Carlos Alberto Hector; Zanuncio, Teresinha Vinha; Guimarães, Edylene Marota; Espindula, Marcelo Curitiba (Pesquisa Agropecuaria Brasileira, 2005)
Species of Scolytidae and Platypodidae were evaluated in a plantation using a clone of Eucalyptus grandis x Eucalyptus urophylla in the State of Minas Gerais, Brazil. Wood disks with galleries were taken from 15 eucalyptus trees between 0.5 and 1.5 m height. After collection, all trees attacked were burned. Woodborers obtained from these disks were identified as Premnobius cavipennis, Premnobius ambitiosus, Dryocoetoides cristatus (Coleoptera: Scolytidae) and Euplatypus parallelus (Coleoptera: Platypodidae). This is the first report of D. cristatus, a Brazilian native species, damaging eucalyptus, which shows its adaptation to this plant.